IN-VITRO Antioxidant Activities of Methnolic Extract of Root of Coleous Vettiveroides (Jacob) - G.GOPALAKRISHNAN; C.K.DHANAPAL; R.MANAVALAN. (International Journal of Pharma and Bio Sciences, 2011)
In vitro antioxidant activities of methanolic extract of tuberous root of coleous vettiveroides (jacob.) was investigated. The free radical scavenging activity to evaluate by DPPH (2,2 -diphenyl -1- picryl hydrazyl) method, Nitric oxide method, Total antioxidant activity. DPPH radical scavenging activity of Methanolic extract and reference standard Rutin IC50 values was found to be 250 mg/ml and 800 mg/ml, nitric oxide scavenging activity of methanolic extract and reference standard ascorpate IC50 values was found to be 510 mg/ml and 490 mg/ml and Total antioxidant activity of methanolic extract was evaluated by phosphomolybdic acid method and reference standard ascorbate IC50 values was found to be 560mg/ml and 585 mg/ml respectively. The above result of possess good antioxidant activity when compared to the above all standards.